Programa de capacitación basado en los procesos conscientes y la gestión curricular en directores de instituciones educativas de Trujillo. - Mera Sabogal, Glariseydi Janett (2019)
ABSTRACT The purpose of this study was to determine the influence of the training program, based on the theory of conscious processes to improve curriculum management of the directors of public educational institutions at secondary level of Trujillo. We worked with a sample population of 20 directors who were selected on a non-probability at the discretion of the investigator. As measuring instruments were applied initial and final pre-test and post-test, then applied the program directors who made up the experimental group, concluding that the training program, based on the theory of conscious processes significantly improved the curriculum planning process in public institutions at the secondary level of Trujillo.